Postextraction Alveolar Preservation and Use of the Crown of the Extracted Tooth as a Temporary Restoration - Andrea Rodríguez Moreno; Mariné Ortiz Magdaleno; Marissa Muñoz Islas; Jorge Armando Villar Mercado; María del Pilar Goldaracena Azuara; Everardo Ruiz Cruz; Gabriel Fernando Romo Ramírez (Case Reports in Dentistry, 2019)
Ranging from the extraction of teeth from anterior sector commitment to the loss of bone and soft tissues, alveolar preservation is a regenerative technique that employs biomaterials that induce the preservation of bone tissue and minimize resorption. Placement of provisional restorations at the defect site maintains the stability of the soft tissues and aesthetics at which the definitive restoration is found. The objective of this clinical case was alveolar preservation postextraction of the anterior tooth that presented a coronal fracture, placing the clinical crown of the extracted tooth as the provisional restoration to maintain stability and to avoid soft tissue collapse and compromise to an aesthetic area.